Every Rig with a One-Variable Fixed Point Presentation is the Burnside Rig of a Prextensive Category - Menni, Matías (2017)
We extend the work of Schanuel, Lawvere, Blass and Gates in Objective Number Theory by proving that, for any L(X) ∈ ℕ[X], the rig ℕ[X]/(X = L(X)) is the Burnside rig of a prextensive category.